PERAN INFRASTRUKTUR JALAN PANTURA JAWA DALAM RANGKA MENDUKUNG PENINGKATAN EKONOMI NASIONAL - Husaini, Hediyanto W.; Junoasmono, Triono (Jurnal HPJI, 2017)
AbstractÂ The Javanese North Coast National Road Corridor, known as âPanturaâ is vital for national economic growth especially in Java Island. The development of The Great Post Road by the government of Hindia Belanda General Governor, Herman Willem Daendels in 1800s become the pioneer of today Panturaâs corridor. Concomitant with the increasing volume of vehicles passing through Pantura, the saturation degree of the corridor is at its limit. Furthermore, inadequate drainage infrastructure alongside Pantura is also one of the factors that worsen road deterioration. Land use around Panturaâs perimeters is densely with industrials complexes and highly populated that makes it difficult for road development and expansion. There are several alternative solutions to reduce the saturation degree of Pantura Java, such as distributing the movement of goods and services into other transportation modes, intersection improvement, law enforcement for over load heavy vehicles, and construct/develop alternative routes. Directorate General of Highways aims to accelerate the construction of Trans Java National Toll Road, expanding and improving other National Corridor Road, such as Central Corridor Road, South Corridor Road, Trans South-South Java and developing ring road in the centers of regional activity in Java.Â Keywords: National Road, Pantura Lane, transportation infrastructure, ring roadÂ Â AbstrakÂ Jalan Pantura merupakan salah satu tonggak utama pertumbuhan perekonomian nasional masyarakat khususnya Pulau Jawa. Pembangunan Jalan Raya Pos oleh pemerintahan Gubernur Jenderal Hindia Belanda, Herman Willem Daendels pada tahun 1800-an menjadi cikal bakal Jalur Pantura saat ini. Seiring dengan pertumbuhan volume kendaraan yang melalui Jalan Pantura, tingkat kejenuhan Jalan Pantura semakin tinggi dan tidak memungkinkan lagi untuk menampung volume kendaraan yang melewati Jalan Pantura. Selain itu infrastruktur drainase di sepanjang Jalan Pantura yang kurang baik juga dapat menjadi salah satu faktor yang mempercepat kerusakan badan jalan tersebut. Kondisi sekitar Jalur Pantura yang padat penduduk dan industri membuat Jalur Pantura sulit untuk dikembangkan. Oleh karena itu solusi untuk mengurangi tingkat kejenuhan Jalur Pantura Jawa, antara lain, adalah dengan mendistribusikan pergerakan barang dan jasa ke moda transportasi lain, melakukan perbaikan simpang, dan meningkatkan law enforcement untuk mengendalikan kendaraan dengan muatan yang melebihi kapasitas badan Jalan Pantura. Sebagai implementasi alternatif solusi tersebut, Ditjen Bina Marga saat ini telah melakukan upaya penyelesaian pembangunan Jalan Nasional Tol Trans Jawa dan penanganan jalan nasional lintas lain, seperti Lintas Tengah, Lintas Selatan, dan Lintas Pantai Selatan Pulau Jawa serta menambah pembangunan jalan lingkar di pusat-pusat kegiatan wilayah di Pulau Jawa.Â Kata-kata kunci: Jalan Nasional, Jalur Pantura, infrastruktur transportasi, jalan lingkar